The Role of Student Organizational Involvement in Shaping Digital Entrepreneurial Intentions - Salsabil, Syifa Hanifa (AL-FALAH : Journal of Islamic Economics, 2024)
Purpose: The study investigates the role that involvement of students in university organizations plays concerning digital entrepreneurial intention among the university students during the digital economy era. The study seeks to understand organizational participation in shaping entrepreneurial skills and mindset among the students. Method: The study design is quantitative in nature. The research sampled 69 computer science students. Analysis uses the TPB, utilizing regression and structural equation modeling to quantify the relationship of student organizational involvement with factors like attitudes, subjective norms, perceived behavioral control, and self-efficacy, added factors namely innovativeness and digital entrepreneurial education. Findings: Results showed that while self-efficacy and student organizational involvement proved to be significant predictors of digital entrepreneurial intention, attitudes, innovativeness, and subjective norms were not. That could suggest a process of developing digital entrepreneurial intentions, which may place more importance on the confidence in one's abilities and active participation in organizations rather than general attitudes or social pressures from the outside. Originality: Unique in its focus on the nexus between student organizational involvement and digital entrepreneurship, this study offers new insights into how universities can foster digital entrepreneurial intentions by enhancing the students' self-efficacy and fostering active engagement in student organizations.